(3TQM CHjGJ eZfi GddHjHs - (3YHO GdbGOQ Hf YeQ GdHZOGOj , J (B1093 (3g` s; (3CHh gTGe GdCfUGQjs ((3CMeO Hf MShfg GdbaUi GdShSi s)
(3ChdgG (B:s
(3hCfTO HYOg hgh GdEfTGO GdKGfi hGdYTQhf HYO GdKdGKeGFI hcd Qajbi cd QMd hCg geG JYGWi GdafG bhekG YeG ENhGf s
(3BNQgG (B:s
(3MJi CfYe Gddg HEHUGQgG aQLYJ ai Jcejd TQM GdCHjGJ hddg GdMeO ChdkG hBNQkG hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg GdWjHjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdg Jedc HGSe eMeO eMehO s
(3Ke hba Ydi YUHJg SfI (B1321 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdCOHs